Mechanisms involved in cardiovascular and hydroelectrolytic changes in dehydrated high-fat-diet-fed rats - Sá, Jéssica Matheus [UNESP]; Fernandes, Marcos Vinícius [UNESP]; Pontes, Roberto Braz [UNESP]; Colombari, Eduardo [UNESP]; Menani, José Vanderlei [UNESP]; Colombari, Débora Simões Almeida [UNESP] (American Physiological Society, 2025)
Obesity is increasingly prevalent worldwide, and climate change is exacerbating water shortages, leading to dehydration. Both obesity and dehydration cause increased arterial pressure (AP), fluid electrolytic imbalance, and neuroinflammation. Thus, the present study aimed to verify the changes in the cardiovascular system, hydroelectrolytic balance, and microglia and neuronal activation in rats fed with a high-fat diet (HFD) in response to 24 h of water deprivation (WD) and the possible mechanisms involved. Male Holtzman rats (290-310 g) were fed with a standard diet (SD, 10% calories from fat) or HFD (46% calories from fat) for 6 wk before the WD experiments. Compared with WD SD rats, WD HFD rats presented a greater c-Fos immunolabeling in the subfornical organ (SFO) and supraoptic nucleus and greater microglial activation in SFO. WD-induced water intake was lower in HFD rats than in SD rats. WD HFD rats presented greater antidiuresis and lesser natriuresis than WD SD rats. Renal denervation did not change the antidiuresis or natriuresis observed in WD HFD- or SD-fed rats. The lower water intake in WD HFD rats might be due to neuroinflammation and/or decreased urinary output. The increase in AP after WD was similar between HFD and SD, but it is more dependent on angiotensin II type 1 (AT1) receptor activation in HFD rats. Overall, HFD rats seem less responsive to fluid and electrolyte balance responses to WD, highlighting the need for strategies to prevent dehydration in individuals with obesity, particularly during rising drought conditions worldwide.NEW & NOTEWORTHY Obesity and dehydration are common worldwide. Our study with an animal model found that changes in arterial pressure are linked to increased activation of the AT1 receptor in obese, dehydrated rats. The renal nerves appear unrelated to the significant decrease in urinary volume and sodium excretion in these animals. Neuroinflammation and reduced urine output may explain their lower water intake. These findings highlight the need for strategies to prevent dehydration in individuals with obesity.
Keywords: AT1R; neuroinflammation; obesity; renal excretion; thirst